Two aspects of models and cultural role of scientific model - Abdul Murad, Mohd Hazim Shah (Arabesques Editions, 2012)
In this paper I will look at the two aspects of models which I call the ‘symbolic’ and the ‘functional’. A comparison is made in this regard between models considered as Kuhnian paradigms, and Durkheim’s theory of social cohesion through collective representation. I argue that models serve a similar function with respect to the scientific community. However, this does not imply that practice is independent of belief. What I suggest instead is that practice is reconciled or negotiated with belief. Thus practice in a sense, does not tell us the whole story.